-3N+3-6N=3

Simple and best practice solution for -3N+3-6N=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3N+3-6N=3 equation:


Simplifying
-3N + 3 + -6N = 3

Reorder the terms:
3 + -3N + -6N = 3

Combine like terms: -3N + -6N = -9N
3 + -9N = 3

Add '-3' to each side of the equation.
3 + -3 + -9N = 3 + -3

Combine like terms: 3 + -3 = 0
0 + -9N = 3 + -3
-9N = 3 + -3

Combine like terms: 3 + -3 = 0
-9N = 0

Solving
-9N = 0

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Divide each side by '-9'.
N = 0

Simplifying
N = 0

See similar equations:

| -4V-3V=-14 | | x(n-3)=4 | | 1+-.5= | | 1+.5x= | | 18x^2-27=35 | | 1.5(x+1)+3.5(x+1)=7.5 | | x^2+5x-10=-3x+10 | | 6x^2+2x-15=34-33x | | 28=4/7w | | 1/2w+3/4w | | 2-2=9x+2x | | 2e^4x-3=5 | | Ln(x)+ln(6)=2 | | 6=8s-3/4-20 | | -1+a/5=-4 | | 6x^2-2x+4=24 | | 8m+3=5m+18 | | x+(x*0.0975)=25 | | x^2-7x+4=-6 | | (-50)x(-4)= | | 5x^2+7x-16=32-27x | | (-8)x(-2)= | | 1200=3x+y | | 25x+70= | | 4=6(x-5)+2-5x | | -0.25+0.75= | | 1/3x+7/6x=220 | | x+9=5(2x-4) | | 5v+7=-23 | | 2k^2-14k-30=k^2+3k+30 | | 22x+100= | | -4(x-1)=-1-4x |

Equations solver categories